LIFELONG EDUCATION: A MODERN VIEW (Innovative professional education, 2024)
In the 21st. century the concept of lifelong learning has become of key importance. It is the answer to the challenge which the world throws at us, where changes happen very quickly. The introduction of lifelong learning is necessary to ensure the dynamics of knowledge generation, increase its influence on the development of science and technology, economic growth and competitiveness.
Keywords: education, studying, development, life